PERSEPSI GURU TERHADAP PENGGUNAAN ORIGAMI DALAM PEMBELAJARAN PRAKARYA DI SEKOLAH DASAR - Rahmi Oktayory Wikarya (Universitas Negeri Padang, 2023)
The purpose of this study was to describe teachers' perceptions of the implementation of origami in craft learning in elementary school. This research is a qualitative research. Qualitative research is research that explores and understands the meaning of a number of individuals or groups of people originating from social problems. Respondents are elementary school teachers. Data collection through questionnaire. All data is collected and analyzed descriptively to obtain reliable and reliable findings. The results showed that teachers' perceptions are very positive towards the use of origami in learning crafts in elementary schools because origami really helps students in practicing motor skills and can foster students' curiosity.